2016
DOI: 10.1097/qad.0000000000001027
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial injury and cognitive function in HIV infection and methamphetamine use

Abstract: Objective In this work we evaluated the association of human immunodeficiency virus (HIV) infection and methamphetamine (METH) use with mitochondrial injury in the brain and its implication on neurocognitive impairment. Design Mitochondria carry their genome (mtDNA) and play a critical role in cellular processes in the central nervous system. METH is commonly used in HIV-infected populations. HIV infection and METH use can cause damage to mtDNA and lead to neurocognitive morbidity. We evaluated HIV infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 51 publications
5
19
0
Order By: Relevance
“…Neuropathological studies showed accumulation of mtDNA damage in the frontal cortex of HAND patients (Zhang et al, 2012), which has implications for the processes of mitochondrial biogenesis and ATP production. A recent study found similar markers of mitochondrial damage in a cohort of HIV+ brains that were stratified by use of methamphetamine (Var et al, 2016). In this study, increased mitochondrial injury in Brodmann area 46 of frontal cortices was associated with worse neurocognitive function in HIV+METH À individuals (Var et al, 2016).…”
Section: Mitochondrial Dysfunction In Neurological Disorderssupporting
confidence: 70%
“…Neuropathological studies showed accumulation of mtDNA damage in the frontal cortex of HAND patients (Zhang et al, 2012), which has implications for the processes of mitochondrial biogenesis and ATP production. A recent study found similar markers of mitochondrial damage in a cohort of HIV+ brains that were stratified by use of methamphetamine (Var et al, 2016). In this study, increased mitochondrial injury in Brodmann area 46 of frontal cortices was associated with worse neurocognitive function in HIV+METH À individuals (Var et al, 2016).…”
Section: Mitochondrial Dysfunction In Neurological Disorderssupporting
confidence: 70%
“…DNA was extracted from CSF supernatant samples using QIAamp DNA Mini Kit (Qiagen, Hilden, Germany) per manufacturer’s protocol. Levels of mtDNA were measured by droplet digital PCR (ddPCR, Bio-Rad, Hercules, CA) using primer-probes combinations targeting the mitochondrial NADH dehydrogenase 2 gene (MT-ND2, Integrated DNA Technologies, IA) and the human genomic DNA (gDNA) by targeting the Ribonuclease P protein subunit p30 gene (RPP30, Integrated DNA Technologies, IA), using ZEN quenched probes [14]. Each sample was run in triplicate in a 20μL of reaction, which consisted of 10μL of 2× Bio-Rad supermix for probes, 1μL of either 20× Primer/FAM-Zen ND2 mix or 20× Primer/HEX-Zen RPP30 mix, 4μL of molecular grade water, and 5μL of total DNA, using the following conditions: (1) an initial activation of 95°C for 10 minutes, (2) 55 cycles of 94°C for 30 seconds and 60°C for 1 min, (3) enzyme inactivation at 98°C for 10 minutes, and 4°C hold.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies using postmortem HIV-infected brains have addressed nuclear DNA methylation, mitochondrial DNA injury, and cerebral gliosis (Desplats et al 2014; Soontornniyomkij et al 2016; Var et al 2016). Epigenetic changes were investigated in the frontal cortex of HIV-infected individuals with or without Meth dependence (Desplats et al 2014).…”
Section: Neuropathologymentioning
confidence: 99%